2016
DOI: 10.2807/1560-7917.es.2016.21.38.30346
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the live attenuated and the inactivated influenza vaccine in two-year-olds – a nationwide cohort study Finland, influenza season 2015/16

Abstract: Although widely recommended, influenza vaccination of children is part of the national vaccination programme only in few countries. In addition to Canada and the United States (US), in Europe Finland and the United Kingdom have introduced live attenuated influenza vaccine (LAIV) for healthy children in their programmes. On 22 June 2016, the US Advisory Committee on Immunizations Practices, voted against further use of LAIV due to no observed vaccine effectiveness (VE) over three consecutive influenza seasons (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
1
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 12 publications
6
54
1
3
Order By: Relevance
“…23 A Finnish cohort study involving 2-year-old children showed a significant vaccine effectiveness against influenza A — predominantly against A(H1N1)pdm09 — of 48% for the quadrivalent live attenuated vaccine and 80% for the trivalent inactivated vaccine. 24 Finally, a U.K. study involving children 2 to 17 years of age showed a non-significant vaccine effectiveness of 42% against A(H1N1)pdm09 for the quadrivalent live attenuated vaccine, as compared with an effectiveness of 100% for the trivalent inactivated vaccine. 25 In light of these data, the ACIP made an interim recommendation not to use the quadrivalent live attenuated vaccine in the United States for the 2016–2017 influenza season.…”
Section: Discussionmentioning
confidence: 99%
“…23 A Finnish cohort study involving 2-year-old children showed a significant vaccine effectiveness against influenza A — predominantly against A(H1N1)pdm09 — of 48% for the quadrivalent live attenuated vaccine and 80% for the trivalent inactivated vaccine. 24 Finally, a U.K. study involving children 2 to 17 years of age showed a non-significant vaccine effectiveness of 42% against A(H1N1)pdm09 for the quadrivalent live attenuated vaccine, as compared with an effectiveness of 100% for the trivalent inactivated vaccine. 25 In light of these data, the ACIP made an interim recommendation not to use the quadrivalent live attenuated vaccine in the United States for the 2016–2017 influenza season.…”
Section: Discussionmentioning
confidence: 99%
“…This article also presents information not provided in the published addenda or statement: figures summarizing the LAIV vaccine effectiveness data from the cited studies, by influenza season and influenza strain, as well as LAIV vaccine effectiveness data used to inform NACI's decision that were not publicly available when the Addendum was finalized, but have subsequently been published (30,31).…”
Section: And the Canadian Immunization Guide Chapter On Influenza Andmentioning
confidence: 99%
“…Among children 2 years of age eligible for vaccination, the LAIV4 VE was 47.9% (significant) for influenza A and 57.2% (non-significant) for B. This compares with an IIV VE of 79.5% for influenza A (significant) and -1% for influenza B (non-significant) 3. It is also noteworthy that previous vaccination with TIV improved VE both for LAIV and TIV.…”
Section: Other Laiv Programmesmentioning
confidence: 82%